Evaluation of visual quality parameters after Descemet membrane endotelial keratoplasty (DMEK) - Gavin Sancho, A.; Romero Sanz, M.; Idoipe Corta, M.; Mateo Orobia, A.; Sanchez Perez, A.; Garcia‐Martin, E.; Satue Palacian, M. (Acta ophthalmologica (Oxford, England), 2017)
Purpose and Objectives To evaluate progressive changes in visual quality parameters in patients who underwent DMEK for Fuchs endotelial dystrophy (FED), and to compare the visual quality results with healthy controls without corneal pathology. Methods Fourteen eyes with FED who underwent DMEK were evaluated for corneal topographic changes using Pentacam (OCULUS, Iberia SL), preoperatively, at 1 month and at 6 months after surgery. Mean keratometry (Km), corneal density (1‐2 mm, central and total), high order aberrations (HOA), low order aberrations (LOA) and total aberrations (total RMS) were analyzed in the anterior and posterior cornea. Fourteen healthy subjects were evaluated using the same protocol and compared with the patient's final evaluation data. Results Significant improvement was observed in patients at 1 month after surgery in the posterior Km (p=0.005), central posterior density (p=0.034), 1‐2 mm posterior density (p=0.006) and central anterior density (p=0.045), and anterior LOA (p=0.026) and total aberrations (p=0.020). After 6 months all densities (anterior and posterior) had improved compared to preoperative results (p<0.05) as well as all posterior aberrations (total, HOA and LOA, p<0.05). Posterior and anterior Km values and corneal densities did not show significant differences compared to healthy subjects (p>0.05). Corneal aberrations (anterior and posterior)remained significantly higher in DMEK subjects (p>0.05) Conclusions DMEK surgery improves corneal visual quality parameters in FED patients after the first month postoperatively. Corneal density and mean keratometry values are not different from healthy corneas at 6 months after DMEK. However, despite corneal aberrations decrease after surgery they remain higher than those values found in healthy corneas.